Plasma Inorganic Pyrophosphate Deficiency Links Multiparity to Cardiovascular Disease Risk - Veiga-Lopez, Almudena; Sethuraman, Visalakshi; Navasiolava, Nastassia; Makela, Barbara; Olomu, Isoken; Long, Robert; van de Wetering, Koen; Martin, Ludovic; Aranyi, Tamas; Szeri, Flora (Frontiers in Cell and Developmental Biology, 2020)
Epidemiological studies indicate that elevated alkaline phosphatase activity is associated with increased cardiovascular disease risk. Other epidemiological data demonstrate that mothers giving multiple childbirths (multipara) are also at increased risk of developing late-onset cardiovascular disease. We hypothesized that these two associations stem from a common cause, the insufficient plasma level of the ectopic mineralization inhibitor inorganic pyrophosphate, which is a substrate of alkaline phosphatase. As alkaline phosphatase activity is elevated in pregnancy, we hypothesized that pyrophosphate concentrations decrease gestationally, potentially leading to increased maternal vascular calcification and cardiovascular disease risk in multipara. We investigated plasma pyrophosphate kinetics pre- and postpartum in sheep and at term in humans and demonstrated its shortage in pregnancy, mirroring alkaline phosphatase activity. Next, we tested whether multiparity is associated with increased vascular calcification in pseudoxanthoma elasticum patients, characterized by low intrinsic plasma pyrophosphate levels. We demonstrated that these patients had increased vascular calcification when they give birth multiple times. We propose that transient shortages of pyrophosphate during repeated pregnancies might contribute to vascular calcification and multiparity-associated cardiovascular disease risk threatening hundreds of millions of healthy women worldwide. Future trials are needed to assess if gestational pyrophosphate supplementation might be a suitable prophylactic treatment to mitigate maternal cardiovascular disease risk in multiparous women.